Evidence for Bartonella quintana in Lice Collected from the Clothes of Ethiopian Homeless Individuals - Tafese Beyene Tufa; Gabriele Margos; Volker Fingerle; Christine Hartberger; Sven Poppert; Richard J. Birtles; Peter Kraiczy; Volkhard A. J. Kempf; Hagen Frickmann; Torsten Feldt (Pathogens, 2023)
Human lice, Pediculus humanus, can transmit various pathogens, including Bartonella quintana, Borrelia recurrentis, and Rickettsia prowazekii. Xenosurveillance is an epidemiological approach to assessing human infection risks performed by screening vectors of infectious disease agents. In the proof-of-principle study reported herein, the DNA of 23 human lice was collected from the clothes of 30 homeless Ethiopian individuals. These samples were assessed using 16S rRNA gene-specific pan-eubacterial PCR for screening, followed by Bartonella genus 16S-23S internal transcribed spacer (ITS) sequence-specific PCR, Bartonella genus gltA gene-specific PCR, and 16S rRNA gene PCR with specificity for relapsing-fever-associated Borrelia spp. with subsequent sequencing of the amplicons. In one sample, the pan-eubacterial 16S rRNA gene-specific screening PCR, the Bartonella genus 16S-23S ITS sequence-specific PCR, and the Bartonella genus gltA gene-specific PCR allowed for the sequencing of B. quintana-specific amplicons. In two additional samples, Bartonella genus gltA gene-specific PCR also provided sequences showing 100% sequence identity with B. quintana. In total, 3/23 (13.0%) of the assessed lice were found to be positive for B. quintana. Correlating clinical data were not available; however, the assessment confirmed the presence of B. quintana in the local louse population and thus an associated infection pressure. Larger-sized cross-sectional studies seem advisable to more reliably quantify the infection risk of lice-infested local individuals. The need for prevention by providing opportunities to maintain standard hygiene for Ethiopian homeless individuals is stressed by the reported findings, especially in light of the ongoing migration of refugees.